Screening of Aspergillus, Bacillus and Trichoderma strains and influence of substrates on auxin and phytases production through solid-state fermentation - Prado, Débora Zanoni do [UNESP]; Okino-Delgado, Clarissa Hamaio [UNESP]; Zanutto-Elgui, Mirella Rossitto [UNESP]; Silva, Richardson Barbosa Gomes da [UNESP]; Pereira, Milene Stefani [UNESP]; Jahn, Linda; Ludwig-Müller, Jutta; Silva, Magali Ribeiro da [UNESP]; Velini, Edvaldo Domingues [UNESP]; Fleuri, Luciana Francisco [UNESP] (Elsevier, 2019)
Crop inoculation with microorganisms is an agricultural technique that has been used to stimulate plant growth and development by different mechanisms, such as the production of P solubilizing enzymes, the phytases, and indole-3-acetic acid (IAA). The aim of the present study is to produce phytases and IAA via solid-state fermentation (SSF) and to correlate biomolecule yield with the characteristics of SSF substrate, such as porosity, water retention, dry mass, electrical conductivity, pH, crude protein, lipids, hemicellulose, cellulose, and lignin for process optimization. Microorganisms belonging to genera Aspergillus, Trichoderma, and Bacillus were cultivated in soybean and wheat bran, in cassava bagasse and in maize and sorghum distiller dried grains with solubles (DDGS). The strains B. subtilis (D), T. atroviride (IOC 4503), and Aspergillus niger (01) produced IAA from tryptophan as shown by LC-MS/MS. All tested microbial genera produced auxins and phytases. The highest indole derivative levels and phytase activity were observed in combinations such as wheat bran/B. subtilis (D) and maize DDGS/T. atroviride, respectively. There were not strong correlations among substrate property, phytase activity and Aspergillus indole compound levels, but there was strong negative correlation between Trichoderma indole derivative and lignin levels. The auxin content in genus Bacillus had strong negative correlation to lignin and strong positive correlation to pH and hemicellulose; therefore, the production of auxin derivatives by genera Trichoderma and Bacillus was improved by substrates presenting low lignin content. In addition, substrates with neutral pH and higher hemicellulose content were recommended to Bacillus.
Keywords: Bioprocessing; Indole-3-acetic acid; Phosphorus; Solid-state fermentation; Tryptophan